2020
DOI: 10.3390/ijerph17165988
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychological Capital Mediates the Association between Burnout and Nursing Performance Outcomes among Hospital Nurses

Abstract: Nursing burnout is associated with reduced nursing performance outcomes. Positive psychological capital is known to play an important role in improving workers’ job performance. However, the association among the three variables has rarely been addressed. The purpose of this cross-sectional descriptive study was to explore the association between burnout and nursing performance outcomes among Korean nurses working at a tertiary hospital and the mediating role of psychological capital in this relationship. Recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 34 publications
2
23
2
1
Order By: Relevance
“…Nurses spend more time with patients than ever before, and patient outcomes are affected by nursing care quality. Excellent nursing job performance ensures that patients are provided appropriate nursing care, and job performance can be included in an evaluation index of nursing quality (An et al, 2020 ). Thus, improvements in nurses' job performance under such special conditions are particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses spend more time with patients than ever before, and patient outcomes are affected by nursing care quality. Excellent nursing job performance ensures that patients are provided appropriate nursing care, and job performance can be included in an evaluation index of nursing quality (An et al, 2020 ). Thus, improvements in nurses' job performance under such special conditions are particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Dwyer et al., (2019) reported that US nurses had moderate psychological capital. An et al., (2020) found that hospital nurses from South Korea experienced middle levels of psychological capital. Previous studies have found that high psychological capital would enhance nurses’ clinical performance, alleviate depression, burnout and turnover intention and increase the quality of clinical care (Brunetto et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…First, the aspects of workload and time pressure were associated with emotional exhaustion. The job overload spent worker capacity to fulfill the needs of work, especially in a few time of rest and recovery (An et al, 2020). The lack individual control in the work environment over goal achievement was closely related to emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…The research finding has referred that burnout was related to nursing performance through mediation of positive psychological capital. Moreover, the result has also said that the nurses who have higher level of positive psychological capital would be less affected by burnout incident and might perform the better nursing care than other coworkers (An et al, 2020).…”
Section: Communicationmentioning
confidence: 98%